2021
DOI: 10.1186/s12879-021-06563-0
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of mobile text reminder in improving adherence to medication, physical exercise, and quality of life in patients living with HIV: a systematic review

Abstract: Background Mobile text reminder (SMS) system is considered a viable strategy for targeting/facilitating healthy behavioural change including adherence to prescribed physical exercises (PE) and medication (antiretroviral therapy-ART) which should improve the quality of life (Qol) in people living with HIV/AIDS(PLWHA). Thus, the literature was appraised for evidence of SMS effectiveness in improving ART and PE adherence behaviours and QoL in PLWHA. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…However future studies should consider incorporating SMS reminders in future studies on anal self-examination as most men in our study chose SMS messaging as a preferred reminder system. This finding was consistent with other studies showing SMS reminders increased the odds of adherence to intervention ( 16 , 17 ). We also found that half of the abnormalities were reported at the start of the study suggesting men were identifying pre-existing abnormalities rather than new abnormalities that developed during the study period.…”
Section: Discussionsupporting
confidence: 93%
“…However future studies should consider incorporating SMS reminders in future studies on anal self-examination as most men in our study chose SMS messaging as a preferred reminder system. This finding was consistent with other studies showing SMS reminders increased the odds of adherence to intervention ( 16 , 17 ). We also found that half of the abnormalities were reported at the start of the study suggesting men were identifying pre-existing abnormalities rather than new abnormalities that developed during the study period.…”
Section: Discussionsupporting
confidence: 93%
“…Like other digital platforms, SMS in and of itself is less characteristic of an intervention and more a platform to deliver information or an intervention. mHealth and eHealth literature has demonstrated that reminder SMS messages are relatively ineffective, but SMS that deliver motivational or informational content or theory-informed content is more effective, particularly SMS platforms that offer interactive instead of one-way communication [ 146 , 147 ]. In this review, included studies ranged in their content and format; de Tolly and colleagues tested different numbers of messages and either motivational or informational content, Nuwamanya and colleagues tested an interactive mobile phone app and Yun and colleagues linked to interactive content on a website through text messages, Salvadori and colleagues sent appointment reminders, and several studies tested informational messages without interaction, which the literature suggests are least likely to produce a desired health action.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, interest has grown in using digital adherence tools (DAT) with reminder cues through short message services (SMS) for improving adherence to treatment and retention in care. (22)(23)(24)(25)(26)(27) Several studies have found DATs with reminder SMS feasible among adult PLHIV. (28)(29)(30)(31) However, there is limited evidence of its effectiveness among CALHIV in improving adherence.…”
Section: Introductionmentioning
confidence: 99%